Elements of Logic and Some Considerations on the Application of Operations on Them - Usarov S.A (Genius Publishing Group, 2022)
This article contains important sections of mathematical science - comments on the basic concepts of mathematical logic (statements that take true or false values) and information about their actions, their application in other disciplines, logical formulas and interpretations of laws in te language.
Keywords: reasoning; reverse disjunction; conjunction; implication